The Relationship Between the Theme and the Characters in the Novel of the Woman at Point Zero by Nawal El Saadawi - Kamayana, I Gusti Nyoman Putra; Dewi, Ni Luh Desy Suari; Dewi, Putu Chrisma (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The novel "Woman at Point Zero" is a novel that predominantly draws on psychological elements. The purpose of this study is to describe: (1) the relationship between theme and character through action, (2) the relationship between theme and character's thoughts, and (3) the relationship between theme and character's feelings. This study uses a qualitative approach. The method used is descriptive analysis. The data consists of linguistic units such as sentences, phrases, and paragraphs related to character's actions, thoughts, and feelings. The data source is the novel "Woman at Point Zero," published by the Obor Indonesia Foundation in 2006. The conclusion of this study is that the theme influenced by action determines humans as supreme beings, the theme influenced by dominant thoughts determines humans as social beings, and the theme's relationship with feelings determines humans as individual beings. This novel depicts the dark side faced by Egyptian women amidst Arab culture steeped in patriarchal values. Women still experience unequal rights and never receive the same rights as men. As in Arab societies, patriarchal culture is one of the foundations of debate over women's status in society, and it continues to generate conflict. The lack of guaranteed women's rights, political freedom, and the hierarchical constraints of husbands leave women disadvantaged in all aspects of life, experiencing discrimination, violence, and poverty.